Pengaruh Potensi Diri Dan Status Sosial Ekonomi Orang tua Terhadap Minat Melanjutkan Pendidikan ke Perguruan tinggi - Muhammad Rio Julianto; Saparuddin Mukhtar; Karuniana Dianta Arpiando Sebayang (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this study was to determine the effect of self-potential, and parents' socioeconomic status on the interest in continuing education to college in class XI students at SMAN 41 Jakarta. The method used is quantitative. The population of this research was class XI students at SMAN 41 Jakarta with a sample size of 99 students. The data used in this study are primary data. Primary data is obtained from distributing questionnaires with 5 alternative answers distributed using Google Forms. The data analysis technique uses multiple regression analysis using SPSS version 25 software. The results showed that: (1) Self-potential has a positive and significant effect on the interest in continuing education to college in class XI students at SMAN 41 Jakarta with a significance value of 0.001. (2) The socioeconomic status of parents has a positive effect on the interest in continuing education to college in class XI students at SMAN 41 Jakarta with a significance value of 0.036, (3) Self-potential and socioeconomic status of parents have a positive effect on the interest in continuing education to college in class XI students at SMAN 41 Jakarta with a significance value of 0.000.